The glamour of prospecting - Cornell, Fred C. (Frederick Carruthers), 1867-1921 (Salt Lake City, UT : Project Gutenberg, 2023)
"The Glamour of Prospecting" by Lieut. Fred C. Cornell is a historical account written in the early 20th century. This narrative chronicles the author$1 (Bs adventures as a prospector in South Africa, detailing his relentless search for valuable minerals like copper, gold, emeralds, and diamonds. The text seamlessly weaves tales of hardships and thrilling explorations in the wild regions of South Africa, giving readers insight into both the beauty and danger encountered in such a precarious profession. At the start of the book, the author introduces his internal struggle with "diamond fever," a passion for the rough stone that drives many to endure difficult and often fruitless journeys in search of fortune. The narrative highlights a series of wild-goose chases, including a significant venture in 1907, where the excitement surrounding diamond discoveries in German South-West Africa leads him and his companions on a grueling expedition. They encounter challenging conditions, dashed hopes, and the harsh realities of prospecting, ultimately returning underwhelmed yet persistent in their quest for discovery. (This is an automatically generated summary.)s
Release date is 2023-04-30
deaurider, PrimeNumber and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: South Africa -- Description and travel; Prospecting; Mines and mineral resources -- South Africa